Comparative analysis of titanium coating on cobalt-chrome alloy in vitro and in vivo direct metal fabrication vs. plasma spraying - Suh, Dongwhan (J Orthop Surg Res, 2020)
BACKGROUND: Titanium surface coating on cobalt-chromium (CoCr) alloy has characteristics desirable for an orthopedic implant as follows: strength, osteointegrative capability, and biocompatibility. Creating such a coated surface takes a challenging process and two dissimilar metals are not easily welded. In our study, we utilized additive manufacturing with a 3D printing called direct metal fabrication (DMF) and compared it to the plasma spraying method (TPS), to coat titanium onto CoCr alloy. We hypothesized that this would yield a coated surface quality as acceptable or better than the already established method of plasma spraying. For this, we compared characteristics of titanium-coated surfaces created by direct metal fabrication method (DMF) and titanium plasma spraying (TPS), both in vitro and in vivo, for (1) cell morphology, (2) confocal microscopy images of immunofluorescent assay of RUNX2 and fibronectin, (3) quantification of cell proliferation rate, (4) push-out biomechanical test, and (5) bone histomorphometry. METHOD: For in vitro study, human osteoblast cells were seeded onto the coated surfaces. Cellular morphology was observed with a scanning electron microscope. Cellular proliferation was validated with ELISA, immunofluorescent assay. For in vivo study, coated rods were inserted into the distal femur of the rabbit and then harvested. The rods were biomechanically tested with a push-out test and observed for histomorphometry to evaluate the microscopic bone to implant ratio. RESULT: For cell morphology observation, lamellipodia and filopodia, a cytoplasmic projection extending into porous structure, formed on both surfaces created by DMF and TPS. The proliferation of the osteoblasts, the DMF group showed a better result at different optic density levels (p = 0.035, 0.005, 0.001). Expression and distribution of fibronectin and Runx-2 genes showed similar degrees of expressions. The biomechanical push-out test yielded a similar result (p = 0.714). Histomorphometry analysis also showed a similar result (p = 0.657). CONCLUSION: In conclusion, DMF is a method which can reliably create a proper titanium surface on CoCr alloy. The resulting product of the surface shows a similar quality to that of the plasma spraying method, both in vivo and in vitro, in terms of biological and mechanical property.